دور إعادة الهندسة الإدارية في محاربة سلبيات البيروقراطية - دوش, الهادي (University of Eloued جامعة الوادي, 2017)
إن تزايد حدة المنافسة وارتفاع مستوى توقعات الزبائن جعل منها حافزا لتحقيق القدرة على تحقيق الأداء والتميز على مستوى إدارة الأعمال، خاصة في ظل انتشار تكنولوجيا الاتصال والمعلوماتية والحكومة الالكترونية وكذا انتشار مفهوم الجودة الشاملة، وبذلك نجد أن هناك الكثير من التحديات التي أصبحت على عاتق هذه الإدارة للقيام بثورة ضد الحلول الإدارية التقليدية التي تركز على التطوير والتحسين التدريجي، لذلك نجد أن أكثر من 70% من شركات الأعمال الأمريكية منذ التسعينات من القرن الماضي قد خطت خطوات جادة في هذا الشأن ونجحت نجاحا باهرا، الأمر الذي استدعى ضرورة التفكير في إمكانية تطبيق أسلوب إعادة الهندسة الإدارية في الإدارة العامة، خاصة وأن أغلب الدول العربية تعاني من مشكلة البيروقراطية وتعقيدات التنظيم الرسمي، فما جدوى تطبيق هذا الأسلوب في الإدارة العامة؟ The increase of the concurrence intensity and the rise of the level of customers expectations on managements level made its rising to realize the ability of accomplishing performance and distinction, especially under the spread of technologies of information and communication and the electronic service, also the spread of the exhaustive quality _ thus, we find many challenges became the responsibility of this administration to carry out a revolution against the traditional administrative solutions that focus on the progressive improvement and development. Therefore, we find that more than 70% of affairs American associations have stepped ahead seriously for this purpose since the ninetieth and have made a great success. the fact called for the necessity of reflection in the possibility of applying the reengineering Business style to the public administration, particularly the majority of had countries suffer from bureaucracy end complexities of the official organization. What is the utility of applying this style in the public administration
The role of administrative re-engineering in the fight against the disadvantages of bureaucracy
مجلة البحوث والدراسات المجلد 14 العدد 02 جامعة الوادي
Keywords: إعادة الهندسة الإدارية، الإدارة العامة، البيروقراطية، التنظيم الرسمي; Reengineering Business, public administration, Bureaucracy, official organization.